Intellectual capital efficiency level of Malaysian financial sector: Panel data analysis (2002-2006) - Nik Muhammad, Nik Maheran; Md Isa, Filzah; Nik Ismail, Nik Rozhan (2008)
Intellectual capital which is encompasses of human capital, structural capital and capital employed has been regarded as a prominent source of competitive advantage of various organizations, which influence the level of innovativeness and creativity that lead to the increase of business performance and a country’s economic growth. Malaysia, as a progressive developing Asian country, must now focus on knowledge driven economy in order to be competitive and capable to face various challenges that exist in the global market. Malaysian financial sectors in particular, need to anticipate and rapidly respond to these demands and expectations in order to maintain their competitive edge in the industry.Therefore, the aim of this study is to examine the efficiency level and the trend of intellectual capital among Malaysian financial sectors and its impact on their company’s value added.Using a model introduced by Pulic (1998) to measure value added intellectual Capital(VAICtm) and panel data analysis to measure the trend of intellectual capital; it was found that out of 18 companies evaluated from year 2002-2006, banking sectors owning more on intellectual capital followed by insurance company and brokerage firm. Company’s value added was very much related to the amount of capital employed as compared to other variables. The trend of intellectual capital shows positive relationship for almost all sectors. However the relationships was found insignificant.